Mutual upper bounds of size and time for a Turing machine and a Markov–Post algorithm for mutual simulations - Kosovskii, N. K.; Kosovskaya, T. M.; Kosovskii, N. N. (Vestnik, St. Petersburg University. Mathematics, 2015)
A Markov–Post algorithm and a Turing machine, which have mutual upper bounds on time and space, are proven to be interchangeable up to a linear function of space and a polynomial of time for the Turing machine, respectively. No more than two-letter extensions of the exterior alphabet are used.